Neglected, Protected, Ejected: Latin American Women Caught by Crimmigration. (July 2017) - Dingeman, Katie; Arzhayev, Yekaterina; Ayala, Cristy; Bermudez, Erika; Padama, Lauren; Tena-Chávez, Liliana
The United States deported 24, 870 women in 2013, mostly to Latin America. We examine life history interviews with Mexican and Central American women who were apprehended, detained, and experienced different outcomes. We find that norms of the "crimmigration era" override humanitarian concerns, such that the state treats migrants as criminals first and as persons with claims for relief second. Removal and relief decisions appear less dependent on eligibility than geography, access to legal aid, and public support. Women's experiences parallel men's but are often worsened by their gendered statuses. Far from passively accepting the violence of crimmigration, women resist through discourse and activism.